ОСОБЕННОСТИ ТЕЧЕНИЯ МУЛЬТИСИСТЕМНОГО ВОСПАЛИТЕЛЬНОГО СИНДРОМА ПРИ КОРОНАВИРУСНОЙ ИНФЕКЦИИ У ДЕТЕЙ - Кабиева, Сауле Маутовна; Ныгызбаева, Шынар Сайлауовна; Мулдашева, Жанар Маратовна; Омирзакова, Перизат Ахметовна; Ахметова, Гульнар Битымовна; Головчик, Елена Михайловна (FORCIPE, 2022)